2021
DOI: 10.1111/tpj.15122
|View full text |Cite
|
Sign up to set email alerts
|

MLK4‐mediated phosphorylation of histone H3T3 promotes flowering by transcriptional silencing ofFLC/MAFinArabidopsis thaliana

Abstract: Casein kinase I (CK1), a ubiquitous Ser/Thr protein kinase in eukaryotes, plays a critical role in higher plant flowering. Arabidopsis CK1 family member MUT9-LIKE KINASEs, such as MLK1 and MLK3, have been shown to phosphorylate histone H3 at threonine 3 (H3T3), an evolutionarily conserved residue, and the modification is associated with the transcriptional repression of euchromatic and heterochromatic loci. This study demonstrates that mlk4-3, a T-DNA insertion mutant of MLK4, flowered late, and that overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Interruption of MLK3 caused early flowering and down-regulation of FLC transcripts, indicating that MLK3 negatively regulates flowering possibly by derepressing FLC expression (Kang et al, 2020). Wang et al (2020c) reported that the nuclear protein MLK4 phosphorylated histone H3 at Thr 3 both in vitro and in vivo. Moreover, a transfer DNA (T-DNA) insertion mutant of MLK4 flowered late, but overexpression of MLK4 caused early flowering.…”
Section: Role Of Phosphorylation In Signal Transduction Of Floweringmentioning
confidence: 99%
See 2 more Smart Citations
“…Interruption of MLK3 caused early flowering and down-regulation of FLC transcripts, indicating that MLK3 negatively regulates flowering possibly by derepressing FLC expression (Kang et al, 2020). Wang et al (2020c) reported that the nuclear protein MLK4 phosphorylated histone H3 at Thr 3 both in vitro and in vivo. Moreover, a transfer DNA (T-DNA) insertion mutant of MLK4 flowered late, but overexpression of MLK4 caused early flowering.…”
Section: Role Of Phosphorylation In Signal Transduction Of Floweringmentioning
confidence: 99%
“…Wa ng et al . (2020 c ) reported that the nuclear protein MLK4 phosphorylated histone H3 at Thr 3 both in vitro and in vivo . Moreover, a transfer DNA (T‐DNA) insertion mutant of MLK4 flowered late, but overexpression of MLK4 caused early flowering.…”
Section: Role Of Phosphorylation In Signal Transduction Of Floweringmentioning
confidence: 99%
See 1 more Smart Citation
“…Since MLK1, MLK2, and MLK4 also functioned as kinases to histone H3 at threonine 3 ( Wang et al, 2015 , 2021 ), we examined the H3T3ph levels. No obvious difference of H3T3ph levels were observed in wild type, mlk1 mlk2 mlk3 , mlk1 mlk2 mlk4 , mlk1 mlk3 mlk4 , and mlk2 mlk3 mlk4 triple mutants ( Supplementary Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…MLK4 interacts with CCA1, and loss of MLK4 functions resulted in late flowering and reduction of H2AS95ph and H2A.Z level at GI ( Su et al, 2017 ). A recent study showed that MLK4 deposited H3T3ph at FLC/MAF ( Wang et al, 2021 ). Phosphoproteomics showed that MLKs phosphorylated proteins in circadian clock, multiple metabolic, and signaling pathways in Arabidopsis ( Wilson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%